A catalogue of the Fanniidae (Diptera) of the Neotropical Region - de Carvalho, C. J.b.; Pont, A. C.; Couri, M. S.; Pamplona, D. (Zootaxa, 2003)
The Fanniidae (Diptera) of the Neotropical Region are catalogued. Two genera and 75 valid species are listed, with references to original descriptions, location of types, geographic distribution, and subsequent taxonomic and applied literature. Mesazelia trichopoda Blanchard, 1942 is a new synonym of Anthomyia pusio Wiedemann, 1830.